MEMBEDAH KEARIFAN SISTEM EKONOMI ISLAM - M. Hasan Ubaidillah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
: The role of economics in Islam is something significant in the course of da'wah Rasu>lulla>h SAW., Because it becomes an alternative solution to the economic problems that are loaded with social inequality. Islamic economics offers the concept of a fair and equitable economy. Thus, one of the successful mission of the Prophet. is because, based on the principles of honesty, fairness, not exploitative. According to Ibn Taymiyya, Islamic economics is the economics of a society that is well equipped, organized on the basis of free enterprise, and personal property with the limits set by moral considerations and supervised by a provision that uphold sharia fair and work for the community. The purpose of the Islamic economic system is nothing but creating welfare and fairness in carrying out activities to happiness bermuamalah world and the hereafter.